The role of plant-derived natural substances as immunomodulatory agents in carcinogenesis - Samec, Marek; Liskova, Alena; Koklesova, Lenka; Samuel, Samson Mathews; Murin, Radovan; Žúbor, Pavol; Bujnak, Jan; Kwon, Taeg Kyu; Büsselberg, Dietrich; Prosecký, Robert; Caprnda, Martin; Rodrigo, Luis; et al. (Journal of cancer research and clinical oncology, 2020)
The role of immune system in carcinogenesis represents fundamental events associated with cancer eradication; however, tumor evolution is connected with various mechanisms of tumor evasion and progression of cancer. Based on recent evidence, phytochemicals are directly associated with immunomodulation of the innate and adaptive immunity via different mechanisms of action including stimulation and amplification of immune cells, humoral compartments, and associated molecules. This comprehensive study focuses on immunomodulating potential of phytochemicals (mixture in plants or separately such as individual phytochemical) and their impact on regulation of immune response during cancer development, immune tolerance, and immune escape. Clinical application of phytochemicals as modulators of host immunity against cancer may represent perspective approach in anticancer therapy.
Keywords: Immune Tolerance; Neoplasms; nádory; Immunity, Innate; karcinogeneze; přirozená imunita; imunologická tolerance; lidé; fytonutrienty; Phytochemicals; imunomodulace; Immunomodulation; Carcinogenesis; Humans